Sarcoidal granulomatous reaction due to tattoos: report of two cases - Martha Cecilia Valbuena; Victoria Eugenia Franco; Lorena Sánchez; Héctor David Jiménez (Anais Brasileiros de Dermatologia, 2017)
Abstract Numerous infectious, inflammatory and neoplastic complications secondary to tattoo placement have been reported in the literature. Within inflammatory complications sarcoidal granulomatous reactions have been described. We report two cases, a 55-year-old woman with yellowish infiltrated plaques on bilateral ciliary region, 16 years after the placement of a permanent tattoo in the eyebrows, and a 20-year-old tattoo artist who developed orange papules on 3 of his tattoos. Histopathology in both cases confirmed diagnosis of sarcoidal granulomatous reaction due to tattoo pigment.